2021
DOI: 10.3390/ijerph18052554
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Preventive Behaviours in Cameroon: A Six-Month Online National Survey

Abstract: Since March 2020, the Cameroonian government implemented nationwide measures to stall COVID-19 transmission. However, little is known about how well these unprecedented measures are being observed as the pandemic evolves. We conducted a six-month online survey to assess the preventive behaviour of Cameroonian adults during the COVID-19 outbreak. A five-point adherence score was constructed based on self-reported observance of the following preventive measures: physical distancing, face mask use, hand hygiene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
4
9
1
1
Order By: Relevance
“…Age influenced COVID-19 preventive behaviors, consistent with previous studies that higher age was a predictor for higher adherence of COVID-19 preventive behaviors ( 24 ). Another study also found that older people were also likely to embrace protective behaviors ( 25 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Age influenced COVID-19 preventive behaviors, consistent with previous studies that higher age was a predictor for higher adherence of COVID-19 preventive behaviors ( 24 ). Another study also found that older people were also likely to embrace protective behaviors ( 25 ).…”
Section: Discussionsupporting
confidence: 90%
“…Experiencing flu-like symptoms influenced COVID-19 preventive behaviors, consistent with previous study that experiencing flu-like symptoms was associated with poor adherence of COVID-19 preventive behaviors ( 24 ). Individuals who experience flu-like symptoms may be more at risk of becoming infected; therefore, continued compliance with preventive behaviors is recommended to reduce the transmission of COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…Target groups to improve overall adherence to the preventive measures should therefore include younger and less educated individuals, particularly in Brazil, Thailand, and the five African countries. In contrast to some previous studies [ 7 , 8 , 10 ], which reported differences in adherence to COVID-19 preventive measures across genders and living status, our study did not find such disparities. However, in a country-stratified analysis, we found that living with other people in Malaysia increased the odds to adherence to more preventive measures.…”
Section: Discussioncontrasting
confidence: 99%
“…The study found that sociodemographic factors (country, Malaysia, Bangladesh; older age and higher education) increased the odds for adhering to more COVID-19 preventive measures. The increased adherence with increasing age and higher education is consistent with previous research [ 1 3 , 8 , 10 ]. As older age is an important risk factor for the severity of COVID-19 illness, it is important to protect older adults from getting infected with COVID-19.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation